Neurofibroma of the stomach without Recklinghausen’s disease: a case report - Mądro, Agnieszka; Kosikowski, Wojciech; Drabko, Jarosław; Rudzki, Sławomir; Słomka, Maria; Fronczek, Agnieszka; Korobowicz, Elżbieta (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Neurofibromas of the stomach can occur in the course of Recklinghausen’s disease. Sporadic gastric neurofibroma appears rarely. This tumour may look like an ulcer and can be a cause of abdominal pain, nausea, and bleeding from the gastrointestinal tract. We reported a 61-year-old women complaining of stomachache for several months. Gastroscopy revealed a tumour with ulceration in the prepyloric part of the stomach. Helicobacter pylori infection was also present. Helicobacter pylori eradication and prolonged treatment of proton pump inhibitors did not decrease the ailments or the size of the tumour. It was not possible to determine the nature and origin of the tumour by carrying out examinations such as endoscopic ultrasound and computed tomography of the abdomen. Only after surgery and histopathological examination with immunohistochemistry was this tumour identified as a neurofibroma. In order to differentiate the tumour the following immunohistochemical examinations were carried out: CD34 (slightly +), CD117 (–), S-100 (+), desmin (–), NSE (+), GFAP (–), SMA (–), bc12 (–), CD99 (–), ALK1 (–), and MiB (1–1.5%). In such cases excision of the tumour is the preferred treatment.